c-Myc: Linking Transformation and Genomic Instability - Prochownik, Edward V. (Current Molecular Medicine, 2008)
CMYC has long been known to be among the most frequently de-regulated oncogenes in human cancer. Only recently, however has a clear understanding begun to emerge of how it promotes transformation. Through its role as a transcription factor, c-Myc alters the expression of hundreds of target genes, many of which are themselves oncogenes or tumor suppressors. The deregulation of c-Myc is both necessary and sufficient for the “acute” type of rapid in vitro transformation that occurs in certain established rodent cell lines. Transformation of primary rodent cells in vitro is also rapid but requires the contribution of at least one additional cooperating oncogene such as Ras. In contrast, the “chronic” form of in vivo transformation by c-Myc is a rare event that requires the acquisition of multiple mutations in other genes affecting cell cycle, senescence, and apoptosis. By greatly accelerating the intrinsic mutation rate at several levels, c-Myc increases the likelihood that these additional mutational “hits” will occur. Among the types of genomic instability mediated by c- Myc are single nucleotide substitutions and double-stranded breaks arising via the induction of reactive oxygen species, gene amplification and the generation of extrachromosomal elements, and numerical chromosomal defects resulting from aberrant DNA synthesis and defects in the mitotic spindle checkpoint. These nonmutually exclusive activities ensure a constant and varied source of genotoxic insults and suggest that c-Myc over-expression imposes a “mutator phenotpye”. This may be an early and necessary requirement for the initial steps in chronic transformation as well as for subsequent evolutionary changes that produce important tumor behaviors such as invasiveness, metastasis, and acquisition of chemotherapy resistance.
Keywords: p16INK4a